1985
DOI: 10.1042/bj2250591
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of creatine kinase BB activity by parathyroid hormone and by prostaglandin E2 in cultured bone cells

Abstract: 1. Bone cells in culture responded to parathyroid hormone (PTH) and prostaglandin E2 (PGE2) by a 2-fold increase in creatine kinase (CK) activity. Combined treatment resulted in a higher response than with PTH alone. Calcitonin (CT) failed to stimulate CK activity, did not affect the response of CK to PTH, but inhibited slightly the increase in CK activity by PGE2. 2. Bone-cell cultures grown in low [Ca2+] (0.125 mM), enriched in PTH-responsive osteoblast-like cells, responded to PTH, but not to PGE2 or CT, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

1988
1988
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 32 publications
1
17
0
1
Order By: Relevance
“…CK regulates the intracellular concentration of ATP by catalyzing the generation of ATP from ADP and phosphocreatine or converts ATP into phosphocreatine. It was demonstrated that in cultured bone cells, PTH is able to increase CK activity (Sömjen et al 1984). Reduced CK level may be found as a consequence of diminished efflux of the muscle enzyme into serum from reduced physical activity (in Orx rats) or may result from reduced muscle mass (fiber size in the present study) accompanying Orx (Rosalski 1998).…”
Section: Discussionmentioning
confidence: 72%
“…CK regulates the intracellular concentration of ATP by catalyzing the generation of ATP from ADP and phosphocreatine or converts ATP into phosphocreatine. It was demonstrated that in cultured bone cells, PTH is able to increase CK activity (Sömjen et al 1984). Reduced CK level may be found as a consequence of diminished efflux of the muscle enzyme into serum from reduced physical activity (in Orx rats) or may result from reduced muscle mass (fiber size in the present study) accompanying Orx (Rosalski 1998).…”
Section: Discussionmentioning
confidence: 72%
“…CK is also present in cartilage and bone cells, PCr is present in chondrocytes as it was demonstrated by 31P-NMR measurements of superfused resting zone cartilage from the growth plates of bones from young animals (56). Bone cells in culture also show B-CK activity when stimulated with Vitamin D metabolites, parathyroid hormone and prostaglandin E2 (57). B-CK has also been shown to be directly and sex-specific stimulated by sex steroids in rat bone indicating that gonodal steroids may contribute to bone growth and to maintaining a balance bone-turnover, with CK being directly involved in the energetics of this process (58,59).…”
Section: Other Tissuesmentioning
confidence: 86%
“…However, specific binding of PTH can be demonstrated only in osteoblasts [5] and osteoclast precursor cells [6], but not in mature osteoclasts. PTH has been shown to have a variety of actions in vitro, such as enhancement of cyclic AMP production [7] and cyclic AMP-dependent protein kinase activity [8], induction of changes in cell shape [9], stimulation of plasminogen activator [10], inhibition of collagen synthesis [11], suppression of alkaline phosphatase activity [12], and stimulation of cell proliferation [13,14] and enzymes associated with cell proliferation [15] such as ornithine decarboxylase [16,17] and the braintype isoenzyme of creatine kinase (CK) [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…As well as increasing adenylate cyclase activity [19], PTH increases the proliferation [13,14] of cultured bone cells, osteosarcoma cells and chondroprogenitor cells [20]. PTH was also shown to modulate phospholipid metabolism [21].…”
Section: Introductionmentioning
confidence: 99%